The Model for Resilience Enhancement with Application Usage of Adolescent: A Systematic Review - Kleawaom, Panita; Kongsuwan, Vineekarn (Princess of Naradhiwas University Journal, 2023)
This literature review aims to summarize the knowledge from the study of resilience enhancement model with application usage of adolescent by researching the articles retrieved from the following database: CINAHL, PubMed, ProQuest, ThaiJO, TDC-ThaiLIS, and Google Scholar from 2012 to 2021. The research data were analyzed using summaries of articles and synthesized by applying the criteria of The Joanna Briggs Institute. The results from synthesizing 10 selected research articles were found that the concepts used as a framework for building a mental strength model consisted of; 1) The concepts about resilience enhancement and the adversity quotient of Grotberg and Carol Ryff 2) The concepts related to the online program called SilverCloud Health, and 3) The related concepts such as Buddhist mental strengthening and integrative counseling. The results of the synthesis revealed that most of activities were group activities to build up mental strength and coping skills. For individual activities were mostly managed in online platform. The activities were also conducted with high school students and university students as the sample group. These models can be applied with adolescent in order to enhance their resilience and overcome the adversity appropriately.